Start at the end : how companies can grow bigger and faster by reversing their business plan - Lavinsky, Dave, 1970- (John Wiley & Sons, 2012)
Re-focus your business plan and achieve the success your business deserves Business owners, and their teams, often lose their way in the midst of the day-to-day stress of generating sales and profits. Whether your goal is selling millions of your product, expanding operations to a new location, or generating more profits, Start at the End offers a unique approach and action steps for business owners and entrepreneurs to redevelop your business plan and achieve ultimate success. You'll learn how to re-create your long-term vision and then make continuous progress in achieving that vision while continuing to hit your short-term goals. Start at the End offers inspiring stories of other entrepreneurs who have achieved significant success in this area, as well as easy-to-follow exercises and next steps. Shows how to develop a realistic business and financial model based on market data Explains how to identify and pursue new opportunities, raise capital, and build growth strategies Start at the End gives business owners a chance to take a step back, re-evaluate your business, and redesign your business plan to achieve the success you dreamed of when you first launched your company.